A gyermekbiblia-kutatás legjelentősebb eredményei - NÉMETH, Dávid (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
The Most Significant Results of the Research on Children’s Bibles. About twenty years ago, Children’s Bibles gained special attention in the field of Religious Education. Since then there has been active research in this field. The historical investigations have revealed a great amount of data unknown before. This study presents the case of the Hübner Bible in Hungary. There has been research concerning the theological and pedagogical aspects based on which the selection of the Biblical stories was made, research about the theological and didactical aspects of the narrative style and also the developmental psychological aptitude on the receiver side that has to be taken into consideration. The types of changes and distortions that differentiate the texts of the Children’s Bibles from the original are also discussed in the study. The quality and the function of the illustrations are also a subject of investigation. Here again the needs and the characteristics of the age group of the children who use the Children’s Bibles is a significant aspect.